PENGEMBANGAN E-LKPD BERBASIS SOCIO SCIENTIFIC ISSUE MENGGUNAKAN APLIKASI LIVEWORKSHEET PADA MATERI TERMOKIMIA KELAS XI SMA/MA SEDERAJAT - Achiryani, Rachmawati Septia; Erviyenni, Erviyenni; Abdullah, Abdullah (UIR Press, 2026)
This study aims to develop a socio scientific issue-based E-LKPD on Thermochemistry material that is valid and receives positive responses from users. The research employed the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. Research data were collected through validation sheets and user response questionnaires. The validation results conducted twice indicated that the E-LKPD was considered highly valid by material and media experts, with percentage scores across various aspects exceeding 96%. User response trials showed positive feedback from both teachers and students, with percentages of 91.41% and 92.29%, respectively. Based on these findings, the E-LKPD is declared valid and positively received, making it feasible for use in Thermochemistry learning.